1986
DOI: 10.1161/01.cir.74.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular filling dynamics: influence of left ventricular relaxation and left atrial pressure.

Abstract: Peak rapid filling rate (PRFR) is often used clinically as an index of left ventricular relaxation, i.e., of early diastolic function. This study tests the hypothesis that early filling rate is a function of the atrioventricular pressure difference and hence is influenced by the left atrial pressure as well as by the rate of left ventricular relaxation. As indexes, we chose the left atrial pressure at the atrioventricular pressure crossover (PCO), and the time constant (T) of an assumed exponential decline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
2
28

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(210 citation statements)
references
References 38 publications
12
166
2
28
Order By: Relevance
“…Many factors can affect mitral flow velocity measurements [26][27][28]. For this reason, we applied a strict selection process for both patients and matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can affect mitral flow velocity measurements [26][27][28]. For this reason, we applied a strict selection process for both patients and matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…26 Isovolumetric contraction time is included in the numerator of the Tei formula and is an important component of pre-ejection period, correlating inversely with +dP/dT. 27 Isovolumetric relaxation time, another component of the Tei formula included in the numerator, corresponds to the time constant of LV relaxation (tau), 28 which is significantly longer in patients with previous MI. 29 The value of tau increases through all stages of diastolic dysfunction, 30 so that isovolumetric relaxation time becomes prolonged with abnormal relaxation in most patients with coronary artery disease.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…A multitude of indices such as peak E and A velocity, their ratio, and acceleration and deceleration times are derived from this velocity pattern and proposed as markers for diastolic function [1][2][3][4][5] . Intensive research, using numerical [6][7][8][9] and in vitro [10] models, next to observations in animals and humans [8,[11][12][13][14][15][16] , have clearly elucidated the physical and physiological determinants of the transmitral velocity pattern. Although it provided us with many clinical useful insights, this research revealed also the limitations of pulsed wave Doppler echocardiography in clinical practice for assessing diastolic function.…”
Section: Introductionmentioning
confidence: 99%